'Lagu patriotik' (patriotic songs) of Malaysia: musical styles and their implications on patriotism - Chan, Cheong Jan; Tan, Keat Shuang (Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, 2014)
‘Lagu Patriotik’ or Patriotic songs have been composed, recorded and broadcast widely since the formation of Malaysia in the 1960s. The sound of patriotic songs like Tanah Pusaka, Putera Puteri, has become the common memory of Malaysian citizens. In school education, patriotic songs were frequently sung and featured in choir competitions. Despite of this long continuity and intense effort of using music to foster nation unity, it is unknown that if these songs have a subtle effect in invoking a sense of belonging and love to the country. Over the years, scattered information from the public has revealed feedbacks that some of the songs have been ‘unattractive’. In addition, the styles of music of the so-called ‘Lagu Patriotik’ are diverse and have changed over the time. It is an intriguing question that if the style of music could influence the emotional effect of the listeners. This paper looks into the body of songs that are known as patriotic songs and attempt to clarify what these songs consists of in terms of its musical content.